2020
DOI: 10.1158/1078-0432.ccr-20-1569
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Potentiates the Therapeutic Efficacy of Docetaxel in Advanced Prostate Cancer by Stimulating NO-cGMP Signaling

Abstract: Purpose: Docetaxel plays an indispensable role in the management of advanced prostate cancer. However, more than half of patients do not respond to docetaxel, and those good responders frequently experience significant cumulative toxicity, which limits its dose duration and intensity. Hence, a second agent that could increase the initial efficacy of docetaxel and maintain tolerability at biologically effective doses may improve outcomes for patients.Experimental Design: We determined phosphodiesterase 5 (PDE5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Similar results were observed in syngeneic cell lines and Pten cKO derived tumoroids where an increase in caspase-3 and PARP cleavage was detected [49]. The combination treatment demonstrated a significant decrease in tumoroid size and growth, with loss of integrity, apoptosis, condensed structure and structural blebbing [50].…”
Section: In Vitro and In Vivo Applications Of Sildenafil In Cancer Treatmentsupporting
confidence: 79%
See 2 more Smart Citations
“…Similar results were observed in syngeneic cell lines and Pten cKO derived tumoroids where an increase in caspase-3 and PARP cleavage was detected [49]. The combination treatment demonstrated a significant decrease in tumoroid size and growth, with loss of integrity, apoptosis, condensed structure and structural blebbing [50].…”
Section: In Vitro and In Vivo Applications Of Sildenafil In Cancer Treatmentsupporting
confidence: 79%
“…The therapeutic combination significantly lowered tumor weight compared to docetaxel alone. Further exploration in the molecular pathways responsible for this phenomenon identified a lower percentage of Ki67-positive nuclei and a higher frequency of cleaved caspase-3 positive cells relative to groups treated with monotherapy, thus promoting apoptosis and tumor regression [50]. Likewise, Hsu, J.-L. et al reported the synergestic effects between vincristine and sildenafil in PC-3-derived cancer xenografts in nude mice demonstrating a decrease in tumor weight relative to the single chemotherapeutic agent [46].…”
Section: In Vitro and In Vivo Applications Of Sildenafil In Cancer Treatmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, the addition of PDE-5i as adjuvant chemotherapy sensitizing agents may work through multiple mechanisms and is not strictly limited to one class of chemotherapeutic agents. Emerging evidence suggests that the sildenafil also improved the efficacy of docetaxel at treating CRPC, which the authors hypothesized was due to improved action of docetaxel on effector pathways, namely cGMP-mediated apoptosis and ERK/JNK downregulation [280]. Although numerous preclinical studies outline the potential roles for PDE-is in anticancer therapy, clinical trials (Table 4) have only begun to show evidence of efficacy [265,281].…”
Section: Phosphodiesterase-inhibitorsmentioning
confidence: 99%
“…Similar results were observed in syngeneic cell lines and Pten cKO derived tumoroids where an increase in caspase-3 and PARP cleavage was detected [ 49 ]. The combination treatment demonstrated a significant decrease in tumoroid size and growth, with loss of integrity, apoptosis, condensed structure, and structural blebbing [ 50 ]. A demonstration between the 3D model translation, compared to the 2D line, further suggests an enhanced probability for in vivo studies and clinical application on patients.…”
Section: In Vitro and In Vivo Applications Of Sildenafil In Cancer Treatmentmentioning
confidence: 99%